2022
DOI: 10.1155/2022/2158516
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Wear Characteristics of AZ91D/Nanoalumina Composites

Abstract: This paper discusses the wear and friction with the 2 W% Al2O3 nanocomposite content of pure Mg and AZ91D Mg alloys. Sliding speeds of 0.5 and 1.5 m/s in cast materials with normal stress conditions have been used in sliding distances up to 2000 m/s (0.5, 1.0, and 1 MPa). In order to evaluate the work hardness of the materials measured on temperature similar to the contact surface, we used hardness patterns and hot-compression flow curves. Mg and AZ91D magnesium alloy pure monolithic Mg are low wear resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Metal matrix composite (MMC) offers a symbiotic blend of properties; this could not be obtained in traditional materials. The MMCs can be attained by combining particulates B 4 C, SiC, Al 2 O 3 , AlN, and Ash into less weight alloys are the preferred to substitute traditional materials in numerous usages defence, structural, automobile, aero-space, marine, and mining industries [1][2][3]. Owing to the less density, better specific strength and better thermal conductivity aluminium alloys are extensively utilized [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metal matrix composite (MMC) offers a symbiotic blend of properties; this could not be obtained in traditional materials. The MMCs can be attained by combining particulates B 4 C, SiC, Al 2 O 3 , AlN, and Ash into less weight alloys are the preferred to substitute traditional materials in numerous usages defence, structural, automobile, aero-space, marine, and mining industries [1][2][3]. Owing to the less density, better specific strength and better thermal conductivity aluminium alloys are extensively utilized [4].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a wide range of metal matrix composites with various mechanical and tribological characteristics have been created. Metal matrix composites from Al6061 were produced by [3] using a hybrid reinforcement of boron nitride and boron carbide. Inorganic and organic ingredients can be combined in a variety of ways to create hybrid materials that have a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi is a great technique for optimising parameters for composite development conferring to [7,8] have shown that a number of variables, including the quantity of strengthened material, processing temperatures, wettability agents, and stirring method, have an effect on the physical and mechanical characteristics of stir cast aluminium alloys. There have been numerous investigations on the mechanical characteristics of metal composites incorporating carbon nanotubes, which have been published [9,10].…”
Section: Introductionmentioning
confidence: 99%